A comparison of the effects of bouldering wall and resistance band activities on upper body strength and grip strength in elementary school children - McNeely, Courtney (My University, 2000)
This study compared the effects bouldering wall activities to resistance band exercises on upper body strength and grip strength in elementary school children. Fifty-five (n = 55) subjects in grades 4-6 participated in the study. The subjects were randomly assigned to the bouldering wall group GI resistance band group. Both groups participated in a training period of 6 weeks During the six weeks, climbers were on the bouldering wall for approximately ten minutes, 2-3 times per week. The subjects who were assigned to the resistance bands performed 8 exercises that trained the muscles of the upper body. These subjects performed 2-3 sets of 12 repetitions for each exercise 2-3 times per week. Pre/post tests for the flexed arm hang and right and left hand grip strength were given to each subject. The ANCOVA results show a significant difference (p < .05) between pre and posttest scores for both males and females in both groups. Chi Square results show that there were significantly fewer participants below the Healthy Fitness Zone, and significantly more in the Healthy Fitness Zone (x' = 8.22, df = 2, p = .016) after treatment. There was not a significant difference (p > .05) between the groups before or after the training period. This study indicated that bouldering wall and resistance band activities were equally effective in developing upper body and grip strength in elementary students.
Keywords: Physical fitness for children; Muscle strength; Grip strength; Indoor rock climbing - Physiological aspects